2018
DOI: 10.1155/2018/6958260
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Spectroscopic Study of Chlorite Minerals

Abstract: The mineral chemistry of twenty chlorite samples from the United States Geological Survey (USGS) spectral library and two other regions, having a wide range of Fe and Mg contents and relatively constant Al and Si contents, was studied via infrared (IR) spectroscopy, near-infrared (NIR) spectroscopy, and X-ray fluorescence (XRF) analysis. More importantly, spectroscopic detection of mineral chemical variations in chlorites provides geologists with a tool with which to collect information on hydrothermal alterat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This observation is supported by the weak band at 7065 cm –1 in the NIR spectra, attributed to the 2ʋAl 2 OH vibration of kaolinite (Petit et al , 1999). In addition, the band at 4525 cm –1 corresponds to the combination of the 2δAl 2 OH and 2ʋAl 2 OH vibrations of kaolinite and/or chlorite (Yang et al , 2018). The presence of chlorite might be verified by the presence of two diagnostic bands at 4280 and 4440 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…This observation is supported by the weak band at 7065 cm –1 in the NIR spectra, attributed to the 2ʋAl 2 OH vibration of kaolinite (Petit et al , 1999). In addition, the band at 4525 cm –1 corresponds to the combination of the 2δAl 2 OH and 2ʋAl 2 OH vibrations of kaolinite and/or chlorite (Yang et al , 2018). The presence of chlorite might be verified by the presence of two diagnostic bands at 4280 and 4440 cm –1 .…”
Section: Resultsmentioning
confidence: 99%
“…According to Shi et al (2018), spectral characteristics of glaucophane can be identified in the NIR region and consequently the blueschist metamorphism can be recognized. Yang et al (2018) described that the wavelength position of the absorption features of chlorites are correlated with the Fe/ (Fe +Mg) values. More specifically, the two diagnostic absorption features of chlorites i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of an absorption band in FTIR spectra depends on the number of the specific bonds present [45].…”
Section: Ft-ir Characterizationmentioning
confidence: 99%